Social Media Marketing Strategies and Customer Engagement Effects on Purchase Intention in Online Business - Wijayanto, Gatot; Risdwiyanto, Andriya; Imawati, Rochimah; Siagian, Ade Onny (International Journal of Business, Law, and Education, 2025)
The rapid expansion of digital platforms has transformed social media into a strategic marketing channel that significantly influences consumer behavior in online business environments. This study examines the relationship between social media marketing strategies and purchase intention, with customer engagement acting as a mediating variable. Using a quantitative research approach, data were collected from active social media users through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social media marketing strategies positively and significantly affect both customer engagement and purchase intention. Additionally, customer engagement demonstrates a strong influence on purchase intention and partially mediates the relationship between social media marketing and purchasing behavior. These findings underscore the importance of designing interactive, credible, and value-oriented marketing content to strengthen consumer engagement and drive purchasing outcomes. The study offers theoretical contributions to digital marketing literature and practical implications for online businesses aiming to enhance marketing effectiveness and customer conversion rates in an increasingly competitive digital marketplace.